Distinguishing between Economies of Scale and Technical Progress - Lawrence J. Lau; Jungsoo Park (International Journal of Empirical Economics, 2022)
We show how economies of scale may be distinguished from technical progress and how both may be simultaneously identified in the empirical analysis of aggregate economic growth. Using the meta-production function framework and a cross-section of time-series macroeconomic data on inputs and outputs from a sample of developed, newly industrialised and developing economies, estimates of their individual degrees of returns to scale and rates of technical progress over different periods are obtained. It is not necessary to assume that the aggregate production functions of all economies are identical — they only need to be similar after suitable economy- and commodity-specific time-varying transformations of the quantities of the measured inputs and outputs, and these similarity assumptions can be and are explicitly tested. In addition, the individual economy-specific biases of returns to scale and technical progress, if any, are also identified. It is found that the degree of returns to scale of an individual economy depends on the size of its domestic market, represented by the size of its population, and the share of industry value-added in its GDP. It is also found that the rates of technical progress of individual East Asian economies depend on their tangible capital intensities.